Склад амфорної тари із затопленої сільської садиби Херсонеса - Туровський, Є.Я. (Археологія, 1995)
Публікується херсонеська амфорна тара, піднята з дна Стрілецької бухти неподалік Херсонеса. Визначаються хронологічні межі знахідки, описуються маловідомі та невідомі раніше клейма, вибиті на ніжках деяких амфор. В статье публикуется херсонесская амфорная тара, поднятая со дна Стрелецкой бухты близ Херсонеса, принадлежавшая археологическому комплексу сельской усадьбы Гераклейского полуострова, руины которой оказались под водой вследствие повышения уровня Черного моря.
Хронологические рамки находки ограничены первой третью III в. до н. э. по данным керамической эпиграфики. На ножках некоторых амфор были оттиснуты малоизвестные и неизвестные ранее клейма в виде букв греческого алфавита, заключенных в круг, овал, квадрат.
Значительная часть поднятых сосудов копирует форму фасосских биконическцх амфор на высокой ножке. The Chersonese amphora package taken from the bottom of the Streletskaya bay near Chersonese which belonged to the archaeological assemblage from the rural estate on the Heraclean Peninsula is described. The ruins of the estate were flooded by water as a result of the Black Sea level rise.
Data of the pottery epigraphies have shown that chronological ranges of the finding mentioned lie within the first thirty years of the 3d cent. B. C. Slightly known and previously unknown marks looking as letters of the Greek alphabet enfolded in a circle, oval and square were stamped on legs of some amphoras. Many vessels taken from the bottom imitate a shape of Fasossian biconical amphoras on a high leg.